Surgery minimizing at median craniofacial tumors - Orest Palamar; Andriy Huk (Ukrainian Neurosurgical Journal, 2013)
Introduction. For surgery minimizing at median craniofacial tumors subcranial surgery is used, in particular endoscopic endonasal surgery or subcranial approach (via frontal sinus).Materials and methods. In 93 patients with malignant craniofacial tumors anterior craniofacial resections was performed: in 63 patients — bifrontal, in 30 — subcranial approach. Histological form and intracranial spread of the tumors was identical in both groups.Results. Total removal when applying subcranial and bifrontal approach differed slightly (respectively 63 and 68%). Indexes of cancer survival do not show significant differences depending on surgical approach (P>0.0500). Postoperative complications were observed more often after bifrontal approach — in 15% patients than after subcranial approach — in 8%. General condition improving was observed in both groups, but after subcranial approach it was significant.Conclusions. Effectiveness of the subcranial approach is similar to that of bifrontal one by surgery radicalism and indexes of overall survival in patients been operated because of malignant craniofacial tumors. At the same time, subcranial surgery of skull base malignant neoplasm is associated with lower frequency of postoperative complications (in our study, twice) and best patients’ state (according to Karnofsky scale).